"Functioning better is doing better": older adults' priorities for the evaluation of assistive technology. - Kabacińska, Katarzyna; Vu, Kim; Tam, Mallorie; Edwards, Olivia; Miller, William C.; Robillard, Julie M. (Assistive Technology, 2023)
Despite the benefits of assistive technology (AT), barriers to technology adoption still exist and are uniquely affecting older populations. Improving technology adoption can be achieved by involving end-users in the development and evaluation process. However, existing AT evaluation tools rarely take into account older adults' experiences. The goal of this study was to fill this gap by determining which AT evaluation criteria are important for older adults. We conducted 4 nominal group meetings with 21 participants aged 50+ in Vancouver, Canada. In the meetings, participants generated AT evaluation criteria and organized them in the order of importance. The content from the meetings was analyzed using qualitative content analysis. Final rankings were collated to reveal which criteria were the most important across the groups. We found that promotion of independence, affordability, ease of use and ethics are the most important AT evaluation criteria for older adults. Some aspects of ATs that older adults value, such as reliability, are not featured in AT evaluation tools. This study provides insight into older adults' priorities for AT evaluation criteria, and concerns that older adults have about AT use. The findings are supplemented with a comprehensive analysis of the group discussions that contextualizes the criteria.